Shengui Sansheng San Ameliorates Cerebral Energy Deficiency via Citrate Cycle After Ischemic Stroke - Luo, Cheng; Bian, Xiqing; Zhang, Qian; Xia, Zhenyan; Liu, Bowen; Chen, Qi; Ke, Chienchih; Wu, Jian-Lin; Zhao, Yonghua (Frontiers in Pharmacology, 2019)
Cerebral energy deficiency is a key pathophysiologic cascade that results in neuronal injury and necrosis after ischemic stroke. Shengui Sansheng San (SSS) has been used to treat stroke for more than three hundred years. In present study, we investigated the therapeutic efficacy and mechanism of SSS extraction on cerebral energy deficiency post-stroke. In permanent middle cerebral artery occlusion (pMCAo) model of rats, it suggested that SSS extraction in dose-dependent manner improved neurological function, cerebral blood flow, 18F-2-deoxy-glucose uptake and the density and diameter of alpha smooth muscle actin positive vasculature in ipsilateral area, as well as decreased infarcted volume. Meanwhile, the metabolomics study in cerebrospinal fluid (CSF) was performed by using 5-(diisopropylamino)amylamine derivatization-ultra-high performance liquid chromatography-quadrupole-time of flight mass spectrometry (DIAAA derivatization-UHPLC-Q-TOF/MS) approach. Eighty-eight endogenous metabolites were identified, and mainly involved in citrate cycle, fatty acid biosynthesis, aminoacyl-tRNA biosynthesis, amino acids metabolism and biosynthesis, etc. The remarkable increase of citrate in CSF after treatment with three dosages indicated that the therapeutic mechanism of SSS extraction might be related with citrate cycle. Simultaneously, it showed that high dosage group significantly increased peripheral blood glucose level, the expressions of glucose transporter (GLUT) 1, GLUT3 and monocarboxylic acid transporter 1, which contributed to the transportation of glucose and lactate. By the regulations of phosphorylated pyruvate dehydrogenase E1-alpha, acetyl CoA synthetase and citrate synthetase, the levels of citrate and its upstream molecules (pyruvate and acetyl CoA) in peri-infarction zone further enhanced, which ultimately caused the massive yield of adenosine triphosphate. Our study first demonstrated that SSS extraction could ameliorate cerebral energy deficiency after ischemia by citrate cycle, which is characterized by the enhancements of glucose supply, transportation, utilization and metabolism.